Saudi Novel: Commencements, Efforts, and Headway (6) - Yahya Saleh Hasan Dahami (Khazanah Pendidikan Islam, 2023)
This article examines the literary success of Ibrahim Al-Humaidan's novel "A Hole in the Garb of the Night" and its significance in developing the Saudi novel. Employing an analytical-critical-descriptive method, the study traces the evolution of the Saudi narrative, highlighting the aesthetic developments and thematic modifications within the genre. By exploring Al-Humaidan's extensive and imaginative work, including novels and short stories, the article sheds light on the characters' interpretations of human behaviour and their interactions with events and mediums. The study emphasizes the social, philosophical, and ideological ends achieved through these interactions, showcasing the notable contributions of Al-Humaidan to the Saudi novel. Ultimately, this research offers valuable insights into the relevance and evolution of the Saudi novel as a significant literary genre.Â